A CFD based comprehensive study of coal-fired updraft gasifier in ceramic industry. (March 2019) - Manek, Bhargav; Javia, M.S.; Harichandan, Atal; Ramani, Hardik
Highlights: CFD simulation and experimental data has been compared for coal fired updraft gasifier. Experimental work has been done on updraft gasifier in ceramic industry. Steady state numerical analysis is carried out with discrete phase modeling. Numerical work is carried out under different equivalence ratios. Synthesis gas species, carbon convergence and cold gas efficiency, effect of steam/air ratio are discussed. Abstract: Coal is the most versatile conventional fuel which was used for many years by human beings for domestic purpose, in heavy industries and power plants. Particular in the ceramic industry, heating requirements have been satisfied by coal. Gasification of coal is the promising and convenient technology of converting the coal into synthesis gas which is a mixture of many combustible species. Gasifier used in present study was updraft type coal-fired gasifier which has been used by ceramic industries of Morbi (India). Experimental works have been carried out for various values of equivalence ratio (E.R.) from 0.24 to 0.36 and for specified boundary conditions. Also, numerical simulations have been compared with experimental works for the same E.R. values and boundary conditions. ANSYS Fluent software has been used to carry out numerical modeling and simulation. For coal-fired gasifier, Euler-Lagrange approach has been used for numerical modeling. The temperature distribution profile on gasifier wall has been compared with experimental and numerical data and it shows good agreement. Optimum E.R. for best syngas quality for Indonesian bituminous type coal was found as 0.28. Syngas composition has been determined at E.R. 0.28 with CO as 23.6 mol%, CO2 as 7.9 mol%, H2 as 19.6 mol%, H2 O as 4.8 mol% and CH4 as 0.3 mol%. Carbon Convergence (C.C.) and Cold Gas Efficiency (C.G.E.) have also been determined in the present study with maximum values C.C. as 97.4% and C.G.E. as 87.5%. Also, the effect of steam/air ratio for E.R. 0.28 has been determined. The increment in steam/air ratio improves hydrogen production but resists overall gasification process.